A game of thrones : the graphic novel. volume 4 - Abraham, Daniel; Martin, George R. R. (Bantam Books, 2015)
The death of King Robert Baratheon and the imprisonment of his Hand, Lord Eddard Stark of Winterfell, has set the great houses of Westeros at one another's throats. In Winterfell, Eddard's eldest son and heir, Robb Stark, has gathered an army and is pushing south, determined to free his father. Along the way, he pledges to marry the daughter of Lord Walder Frey in exchange for a military advantage that allows him to capture Jaime Lannister - a powerful bargaining chip to ensure Lord Eddard's safe release. But it is one thing to capture the Kingslayer and quite another to hold him. Meanwhile, in King's Landing, young King Joffrey has other ideas than an exchange of prisoners. Ignoring the advice of his mother, Queen Cersei, he throws oil on the flames of conflict and ignites a conflagration that seems likely to consume not only the Starks but all of Westeros - unless Tyrion Lannister, the Imp, can bring the mad boy-king to heel. Beyond the Wall, greater dangers are brewing, as a winter as brutal as any in history approaches, bringing with it unnatural creatures out of legend. There, Eddard's bastard, Jon Snow, must decide once and for all where his loyalties lie. And across the Narrow Sea, Daenerys Targaryen will learn the true measure of grief - and emerge from its fiery depths transformed, hardened, and ready to claim what is hers by right: the Iron Throne.